Impact of probiotics on chicken gut microbiota, immunity, behavior, and productive performance—a systematic review - Idowu, Peter A.; Mpofu, Takalani J.; Magoro, Aletta M.; Modiba, Mamokoma C.; Nephawe, Khathutshelo A.; Mtileni, Bohani (Frontiers in Animal Science, 2025)
The poultry industry is continuously seeking strategies to improve chicken health, welfare, and productivity while minimizing the use of antibiotics. Probiotics, as a natural alternative, have gained considerable attention due to their ability to modulate the gut microbiota, enhance immune function, and improve productive performance. The aim of this article is to provide updated information on the importance of probiotics in chicken. To achieve this, a systematic review was conducted to synthesize current findings on the impact of probiotics on chicken gut microbiota composition, immune responses, behavior, productive traits, and meat quality using literature databases such as PubMed, CABI Abstract, Google Scholar, and ScienceDirect from April 2010. The PRISMA method was adopted, where 85 articles met the criteria for this review article after several exclusion criteria. The review stated that due to the influence of the intestinal microbial balance, probiotics promote beneficial bacterial populations, suppress pathogens, improve gut health, and enhance nutrient absorption, improving growth performance. Additionally, the immunomodulatory effects of probiotics help strengthen the chicken’s immune system, reducing disease susceptibility. Moreover, recent studies suggest that probiotics may positively influence chicken behavior, particularly by reducing stress, enhancing overall health, and improving welfare conditions. This review also addresses gaps in knowledge, highlighting areas where further research is needed to optimize probiotic use in poultry production systems. Understanding both the short- and long-term effects of probiotics on chicken health and performance will provide critical insights for developing sustainable strategies to boost poultry industry outcomes.